Seasonal changes in gross efficiency and aerobic capacity in well-trained road cyclists - Ploszczyca, K.; Foltyn, J.; Goliniewski, J.; Krezelok, J.; Poprzecki, S.; Ozimek, M.; Czuba, M. (Isokinetics and Exercise Science, 2019)
BACKGROUND: The purpose of this study was to evaluate changes to key aerobic performance determinants, namely maximal oxygen uptake (VO 2max ), lactate threshold (LT) and gross efficiency (GE) over the cycling season. METHODS: Twelve well-trained road cyclists completed three incremental tests during a season in order to determine VO 2max , LT and GE. The laboratory tests were performed using the following sequence: after the transition period (TRAN), during the preparatory period (PREP) and during the competition period (COMP). RESULTS: VO 2max did not change significantly over the season. Workload at lactate threshold (WL LT ) increased by 11% between the TRAN and COMP periods (p < 0.001), which was accompanied by an increase in oxygen uptake at lactate threshold (VO 2LT ; p < 0.01). The percentage of VO 2max at the LT changed from 80.1% to 85.6% (p < 0.05). GE increased from 21.9 ± 1.1% in TRAN to 22.8 ± 0.8% in COMP (p < 0.01). No significant correlations were found between VO 2max and GE and between changes in GE and those in VO 2max in any training period. CONCLUSIONS: In well-trained athletes, the training process contributes mostly to improvements in submaximal indicators, while it does not change VO 2max . GE is an indicator that is expected to improve over the season, but further research is needed to explain the mechanisms responsible for the individual fluctuations of the GE value in athletes.